The Effects of YKS Yuk Kenali SADARI Comic Media on the Knowledge of Self-Breast Examination (SADARI) in Female Students of Grade X at SMA 4 Purwokerto - Aminatun, Khaniroh; Linggardini, Kris (Proceedings Series on Health & Medical Sciences, 2024)
Background: Breast cancer is the most common cancer in women. One of the efforts to reduce or prevent the incidence of breast cancer is early detection through Self-Breast Examination (SADARI). Increasing the knowledge of teenage girls can be achieved using various media, including comics. Method: This research used a quantitative approach with a pre-experimental design, specifically the one-group pre-post-test design. The analysis used in this research is descriptive analysis. The sample consisted of 73 female students of Grade X at SMA 4 Purwokerto, selected using simple random sampling. The research instrument used was a modified closed questionnaire. Results: The results of this study showed that the level of knowledge before the intervention was categorized as low (58.9%). After the intervention, the level of knowledge increased significantly to good (86.3%). The Paired t-test showed a p-value of 0.000. Conclusion: The YKS Yuk Kenali SADARI comic media significantly increase the knowledge of Self-Breast Examination (SADARI) in female students of Grade X at SMA 4 Purwokerto.